How are streamflow responses to the El Nino Southern Oscillation affected by watershed characteristics?. Issue 5 (31st May 2017) - Rice, Joshua S.; Emanuel, Ryan E.
Abstract: Understanding the factors that influence how global climate phenomena, such as the El‐Nino Southern Oscillation (ENSO), affect streamflow behavior is an important area of research in the hydrologic sciences. While large‐scale patterns in ENSO‐streamflow relationships have been thoroughly studied, and are relatively well‐understood, information is scarce concerning factors that affect variation in ENSO responses from one watershed to another. To this end, we examined relationships between variability in ENSO activity and streamflow for 2731 watersheds across the conterminous U.S. from 1970 to 2014 using a novel approach to account for the intermediary role of precipitation. We applied an ensemble of regression techniques to describe relationships between variability in ENSO activity and streamflow as a function of watershed characteristics including: hydroclimate, topography, geomorphology, geographic location, land cover, soil characteristics, bedrock geology, and anthropogenic influences. We found that variability in watershed scale ENSO‐streamflow relationships was strongly related to factors including: precipitation timing and phase, forest cover, and interactions between watershed topography and geomorphology. These, and other influential factors, share in common the ability to affect the partitioning and movement of water within watersheds. Our results demonstrate that the conceptualization of watersheds as signal filters for hydroclimate inputs, commonly applied to short‐term rainfall‐runoff responses, also applies to long‐term hydrologic responses to sources of recurrent climate variability. These results also show that watershed processes, which are typically studied at relatively fine spatial scales, are also critical for understanding continental scale hydrologic responses to global climate. Key Points: Treating precipitation as an intermediary facilitates examination of watershed scale variability in hydrologic responses to ENSO The characteristics of watersheds are an important influence on how they respond to ENSO Ongoing hydroclimate changes may yield increasingly strong responses to ENSO in the future